Pengaruh Rasio Intermediasi Makroprudensial, Dan Ukuran Perusahaan Terhadap Return On Assets Dengan Manajemen Laba Sebagai Variabel Intervening - Hermanto Hermanto; Nurhidayah Nurhidayah (JEMAP, 2023)
The purpose of this study is to see the effect of Macroprudential Intermediation Ratio (RIM), firm size on Return on Assets with earnings management as an intervention variable. The current study utilizes information taken from the financial statements of banks listed on the BEI using a purposive sampling test method that meets the exploratory steps. The researcher studied for a period of five years using a sample of 120 data from 24 banking sector entities. This study uses Partial Least Square (PLS) with secondary data types. From the results in this study partially negative effect of Macroprudential Intermediation Ratio (RIM) on Return On Assets, then firm size has a positive effect on Return On Assets, Macroprudential Intermediation Ratio (RIM) can have a negative influence on management earnings, firm size has a positive effect on earnings management and earnings management has a negative effect on Return On Assets. Earnings management is able to mediate the relationship between Macroprudential Intermediation Ratio (RIM) on Return On Assets and earnings management is not able to mediate firm size on Return On Assets.